Immunologic and inflammatory consequences of SARS-CoV-2 infection and its implications in renal disease - Naiditch, Hiam; Betts, Michael R.; Larman, H. Benjamin; Levi, Moshe; Rosenberg, Avi Z. (Frontiers in Immunology, 2025)
The emergence of the COVID-19 pandemic made it critical to understand the immune and inflammatory responses to the SARS-CoV-2 virus. It became increasingly recognized that the immune response was a key mediator of illness severity and that its mechanisms needed to be better understood. Early infection of both tissue and immune cells, such as macrophages, leading to pyroptosis-mediated inflammasome production in an organ system critical for systemic oxygenation likely plays a central role in the morbidity wrought by SARS-CoV-2. Delayed transcription of Type I and Type III interferons by SARS-CoV-2 may lead to early disinhibition of viral replication. Cytokines such as interleukin-1 (IL-1), IL-6, IL-12, and tumor necrosis factor α (TNFα), some of which may be produced through mechanisms involving nuclear factor kappa B (NF-κB), likely contribute to the hyperinflammatory state in patients with severe COVID-19. Lymphopenia, more apparent among natural killer (NK) cells, CD8+ T-cells, and B-cells, can contribute to disease severity and may reflect direct cytopathic effects of SARS-CoV-2 or end-organ sequestration. Direct infection and immune activation of endothelial cells by SARS-CoV-2 may be a critical mechanism through which end-organ systems are impacted. In this context, endovascular neutrophil extracellular trap (NET) formation and microthrombi development can be seen in the lungs and other critical organs throughout the body, such as the heart, gut, and brain. The kidney may be among the most impacted extrapulmonary organ by SARS-CoV-2 infection owing to a high concentration of ACE2 and exposure to systemic SARS-CoV-2. In the kidney, acute tubular injury, early myofibroblast activation, and collapsing glomerulopathy in select populations likely account for COVID-19-related AKI and CKD development. The development of COVID-19-associated nephropathy (COVAN), in particular, may be mediated through IL-6 and signal transducer and activator of transcription 3 (STAT3) signaling, suggesting a direct connection between the COVID-19-related immune response and the development of chronic disease. Chronic manifestations of COVID-19 also include systemic conditions like Multisystem Inflammatory Syndrome in Children (MIS-C) and Adults (MIS-A) and post-acute sequelae of COVID-19 (PASC), which may reflect a spectrum of clinical presentations of persistent immune dysregulation. The lessons learned and those undergoing continued study likely have broad implications for understanding viral infections’ immunologic and inflammatory consequences beyond coronaviruses.